Implementation Of Smart Techno Parenting in Shaping Children's Character to Face the Industry 5.0 Era - Purba, Nursenta Dahliana; Putri Nome, Davi Cristika (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
The use of gadgets as playmates for children has become increasingly common among modern parents. This trend has led to a shift in the parental role as play companions, especially during the developmental stage of children aged 1-5 years, known as the